Effect of Eco Enzymes Dilution on the Growth of Turi Plant (Sesbania grandiflora) - Ginting, N. A.; Ginting, N.; Sembiring, I.; Sinulingga, S. (Jurnal Peternakan Integratif, 2021)
Eco Enzymes (EE) is one of the products of fermentation that comes from fruits and vegetables wastes. Enzymes and organic acid in Eco Enzymes has a positif effect on plant growth. This study aims to investigate dilution of Eco Enzymes and its application to improve the growth of Turi plants. This research used the completely randomized design method (CRD). The treatments consisted of P1 (1:300), P2 (1:200), dan P3 (1:100), and there were 5 replications. Parameters were plant height, stem diameter, number of branches, number of leaves and leaf width. The results of this research were that 1:100 dilution treatment had significant effect (p<0,05) on the the parameters of plant height, stem diameter, number of leaves and leaf width. However there was no significant effect on the number of branches. The best response to Eco Enzymes was 1: 100 dilution.